Gender pay gap in Poland - Michal Grajek (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
The gender pay gap under central planning and its changes in the course of transition have only lately attracted the attention of researchers. Only few papers focused on comparison between two economic regimes, pre and post reform, having reported narrowing gap for all East European countries. This paper adds more detailed study of timing of the gap changes to existing evidence. This in turn allows to identify which mechanisms of transition were responsible for these changes. It investigates the earnings gap between females and males in Poland over the years 1987-1996, i.e. in the last years of central planning and during the period of transition to market economy. The JMP decomposition, which accounts for changes in overall wage dispersion over time beyond Oaxaca.s standard decomposition, is applied on large set of HBS data and reveals some interesting results. The year of giving away the power by the communists (1989) turned out to be far more important in terms of improving relative position of women than the actual year of launching the reform package (1990) and all the following years of transition. Females had gained substantially due to the structural shift in the very first years of the new economic system and the improvements have slowed down or even reversed in the next years, probably due to the .statistical. discrimination. – – Die Entwicklung geschlechterspezifischer Einkommensunterschiede während des Übergangs von der zentralistischen Planwirtschaft zur Marktwirtschaft wird erst seit kurzem in der Forschung thematisiert. Die wenigen Arbeiten, die Einkommensdifferenzen zwischen den beiden Wirtschaftsystemen . vor und nach der Reform . untersuchen, weisen auf einen abnehmenden Abstand in allen mittel- und osteuropäischen Ländern hin. Der vorliegende Beitrag ergänzt die Forschung nicht nur um eine detaillierte Analyse des Anpassungsverlaufs der Einkommenslücke, sondern identifiziert auch die Ursachen dieser Entwicklung. Die Untersuchung, die anhand von haushaltsbezogenen Einkommensunterschieden zwischen Frauen und Männern in Polen erfolgt, berücksichtigt die letzten Jahre der zentralen Planwirtschaft und die Übergangszeit (1987-1996). Die Juhn-Murphy-Pierce-Zerlegung (JMP-Zerlegung), die im Gegensatz zur Oaxaca-Methode explizit Änderungen in der allgemeinen Einkommensverteilung berücksichtigt, wurde auf die umfangreichen Haushaltsdaten angewendet. Die Ergebnisse zeigen, daß es 1989, dem Jahr der Beendigung der kommunistischen Führung, zu einer wesentlich stärkeren Verbesserung der relativen Einkommensposition der Frauen kam, als im folgenden Jahr, in welchem die Wirtschaftsreformen tatsächlich verabschiedet wurden. Insgesamt profitierten Frauen erheblich vom Strukturwandel der ersten Jahre nach der politischen Wende. Dieser Aufholprozeß verlangsamte sich später, wahrscheinlich durch einen statistischen Diskriminierungseffekt.
Keywords: J71; 330; Earnings Differentials; Discrimination; Gender; Decomposition; Transition economy; Planned economy; Poland